Fibroblast growth factor 8 and cell proliferation in zebrafish fins. - Poleo Camejo, German Antonio. (University of Ottawa (Canada), 1998)
The fins of some teleost fishes, like many urodele amphibian limbs, have the ability to regenerate after injury. This regeneration process occurs in a sequential manner beginning with the closure of the wound by epithelial cells and followed by the establishment of a region of undifferentiated proliferating mesenchymal cells called the blastema. To examine the pattern of cell proliferation taking place in the different tissues during the regeneration process of zebrafish (Danio rerio) caudal fins, I followed the pattern of incorporation of bromodeoxyuridine (BrdU) in the DNA of proliferating cells at various times after amputation. Growing evidence suggests that key molecules involved in signaling pathways leading to limb bud development are also acting during fin bud development. Some of these signals are members of the fibroblast growth factor (Fgf) gene family which locally regulate growth and patterning in vertebrate embryos and during limb regeneration. I sequenced a cDNA clone encoding for the zebrafish FGF8 protein and analyzed its pattern of expression during zebrafish embryonic development and during fin regeneration. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.